1995
DOI: 10.1161/01.cir.91.6.1659
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-Day Mortality in the Era of Reperfusion for Acute Myocardial Infarction

Abstract: The clinical determinants of mortality in patients treated with thrombolytic therapy within 6 hours of symptom onset are multifactorial and the relations complex. Although a few variables contain most of the prognostic information, many others contribute additional independent prognostic information. Through consideration of multiple characteristics, including age, medical history, physiological significance of the infarction, and medical treatment, the prognosis of an individual patient can be accurately esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
312
2
13

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(343 citation statements)
references
References 48 publications
16
312
2
13
Order By: Relevance
“…In the INTERHEART study, the strength of the association of hypertension with risk of first myocardial infarction (MI) was greater in women than in men [6]. Hypertension is also an important risk factor for death and ischemic events after presentation with acute coronary syndromes (ACS) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the INTERHEART study, the strength of the association of hypertension with risk of first myocardial infarction (MI) was greater in women than in men [6]. Hypertension is also an important risk factor for death and ischemic events after presentation with acute coronary syndromes (ACS) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the impact of hypertension in patients with ST elevation myocardial infarction (STEMI) are so far inconsistent, and are mainly related to studies performed in the thrombolytic era [7,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that admission heart rate (HR) values independently predict mortality in patients with ST-elevation acute myocardial infarction (STEMI). [1][2][3][4][5][6][7][8][9] Recently, Boersma et al identified HR as a significant predictor of 30-day mortality in patients with ACS without persistent ST-segment elevation. 10 However, there are no data regarding the long-term predictive value of the initial HR in patients with the full spectrum of ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Lee et al demonstrated in the GUSTO‐I (Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries‐I) that both heart rate and BP are among 5 predictors of 30‐day mortality after acute myocardial infarction 23. Contemporary findings in the field of cardiology showed similar results; in a cohort of 7187 patients with ST‐segment elevation–myocardial infarction, admission SI ≄0.7 was also associated with 1.6‐ and 1.5‐fold increased risk of 7‐ and 30‐day major adverse cardiovascular events, respectively 5…”
Section: Discussionmentioning
confidence: 99%